A frequency-dependent variable damping control method for base-isolated structures under ground motions with different frequency characteristics. Issue 165 (February 2023) - Li, Zhong-Xian; Wen, Dongbin; Shi, Yundong; Wei, Xin; Liu, Biao
Abstract: The base isolation technique is commonly adopted to protect important structures from earthquake damages. Typically, a high damping ratio for the base isolation layer is useful in reducing the structure's resonance effect under low-frequency (long-period) ground motions, and a low damping ratio is preferred in minimizing the acceleration response under high-frequency (short-period) ground motions while not causing significant displacement response. To realize optimal control for base-isolated structures under ground motions with different frequency characteristics, the semi-active control is adopted and a frequency-dependent variable damping (FVD) control method based on a transmissibility weighted fast Fourier transform (TWFFT) spectrum is newly proposed. The FVD control method considers the influences of different frequency components of ground motions on base-isolated structures by developing the TWFFT spectrum of the detected ground accelerations. A series of shaking table tests for a base-isolated steel frame structure with semi-active control were carried out to evaluate the effectiveness of the FVD control method. The test results demonstrated that the FVD control method could realize optimal control of the structure under various types of ground motions, and it was more effective than the ON-OFF control method which only considered the dominant frequency characteristics of the ground motions. Highlights: A transmissibility weighted FFT spectrum considering the information of the structure and the ground motion is developed. A frequency-dependent variable damping control method based on the transmissibility weighted FFT spectrum is proposed. Shaking table tests are conducted to investigate the effectiveness of the control method under various ground motions.